Infinitive consequential constructions - Luka Vukojević (Rasprave: Časopis Instituta za Hrvatski Jezik i Jezikoslovlje, 2008)
Infinitive consequential constructions can be divided according to a few criteria – primarily into phraseological and non-phraseological constructions. According to their place in the sentence, they can be divided into free sentence structures and structures which are a clause. Infinitive constructions are further divided into prepositional and non-prepositional sentence constructions. All infinitive consequential constructions are of the correlative type. Nonprepositonal infinite constructions are relatively rare. The phrase adjective + za + infinitive in the sentence e.g. Lijepa je za pošizit (She is so beautiful you could go crazy) differs greatly in many features from constructions which are similar at first glance, such as Krleža je težak za čitati (Krleža is difficult to read). In such phrases, preposition+infinitive limits or in some other way determines the range of meaning of the adjective which precedes it. There is a special syntactic type of preposition + infinitive constructions in which the phrase za + infinitive appears after the copula in the attributive position. To je za umrijet od smijeha (It is so that you could die laughing). To je za prste polizat (It is so that you could lick your fingers). Such infinitive phraseological constructions and expressions appear with a very small number of verbs of mostly negative semantics. All consequential infinitival constructions are a surface remnant of the sentence inserted into the prepositional phrase generated in the adjectival specifier. The subject of such sentences is almost without exception the expletive to. Most infinitive constructions are generated by phraseological consequential constructions, i.e. structurally and semantically blocked constructions. Such constructions have a permanent structure, range of usage and motivation. These are always emotional and expressive constructions with an intensificational meaning. Phraseological consequential constructions za + infinitive are degree modifiers.